2014
DOI: 10.1111/j.1532-950x.2014.12234.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Axial Radioulnar Incongruence With Cartilage Damage in Dogs With Medial Coronoid Disease

Abstract: Axial RUI is greater and more prevalent in elbows with severe cartilage disease, and consists most commonly of a short radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 25 publications
3
49
0
Order By: Relevance
“…Our results are also in accordance with the amount of radio-ulnar translation reported in a cadaveric model of simulated triceps pull (Might et al, 2011). Therefore, the widely suspected dynamic radio-ulnar step creation during weight bearing activity (Gemmill et al, 2005;Kramer et al, 2006;Gemmill and Clements, 2007;Smith et al, 2009;Might et al, 2011;Gutbrod and Guerrero, 2012;Starke et al, 2013Starke et al, , 2014Krotscheck et al, 2014a;Mariee et al, 2014;Eljack and Bottcher, 2015) is a consistent physiological pattern of elbow kinematic in dogs. While the results of the current data prove the presence of dynamic RUI in canine elbow joints, the amplitude of dynamic translation was not different between normal and dysplastic joints.…”
Section: Imaging Findings Radiography and Ctsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results are also in accordance with the amount of radio-ulnar translation reported in a cadaveric model of simulated triceps pull (Might et al, 2011). Therefore, the widely suspected dynamic radio-ulnar step creation during weight bearing activity (Gemmill et al, 2005;Kramer et al, 2006;Gemmill and Clements, 2007;Smith et al, 2009;Might et al, 2011;Gutbrod and Guerrero, 2012;Starke et al, 2013Starke et al, , 2014Krotscheck et al, 2014a;Mariee et al, 2014;Eljack and Bottcher, 2015) is a consistent physiological pattern of elbow kinematic in dogs. While the results of the current data prove the presence of dynamic RUI in canine elbow joints, the amplitude of dynamic translation was not different between normal and dysplastic joints.…”
Section: Imaging Findings Radiography and Ctsupporting
confidence: 88%
“…Radio-ulnar incongruence (RUI) has been reported to occur concomitant to medial coronoid disease in up to 60% of clinical cases and has been shown to be related to the severity of medial compartment pathology (Eljack and Bottcher, 2015). Traditionally RUI has been defined as two forms of incongruence: (1) an abnormal shape of the trochlear notch of the ulna, leading to humero-ulnar incongruence (Wind, 1986;Wind and Packard, 1986) or (2) a step formation between the articular surfaces of the radius and ulna (short ulna or short radius), leading to radio-ulnar incongruence and secondary to this humero-ulnar conflict.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1980's, elbow incongruity was identified as a likely cause of MCPD (Wind , Wind & Packard ) but subsequent CT studies have revealed that there may or may not be incongruity of the elbow joint at the time of diagnosis (Gemmill et al . , Eljack & Böttcher ) and its exact contribution to the development of medial coronoid articular lesions remains incompletely understood. Axial incongruity can be defined as positive or negative; the ulnar articular surface either being proximal or distal to the radial articular surface, respectively (Lozier ) and may be observed at both the apex (Gemmill et al .…”
Section: Introductionmentioning
confidence: 99%